Creative Solutions for Higher Education Research Issues In Asia and Beyond - Padua, Roberto N. (JPAIR Institutional Research, 2013)
The current system of journal metrics adopted by most Western countries appears to marginalize many Asian and Latin American authors. Impact factors (both at the author and journal levels) rely heavily on citation indices which, understandably, favor Western authors. Of course, impact factors are used heavily in research funding decisions. Creative solutions are explored in this paper for Asian countries experiencing these problems.Keywords: journal metrics, impact factor, citation indices.
Keywords: journal metrics; impact factor; citation indices; Education; descriptive design; Philippines